Novel ocular observations in a child with Joubert syndrome type 6 due to pathogenic variant in TMEM67 gene - Maram EA Abdalla Elsayed; Syed M. Ali; Carly Gardner; Igor Kozak (American Journal of Ophthalmology Case Reports, 2024)
Purpose: To describe unique ocular features in a child with Joubert syndrome type 6. Observations: A 4-year-old male patient presented with right microphthalmia and non-dilating pupil and left primary position nystagmus. Brain MRI revealed a “molar tooth sign” of the midbrain and a “batwing sign” of the fourth ventricle along with large retroorbital cysts bilaterally. The diagnosis of autosomal recessive Joubert syndrome type 6 due to homozygous pathogenic variant c.725A > G p. (Asn242Ser) in TMEM67 gene was confirmed by whole exome sequencing. Left eye had nystagmus and the left optic nerve and retina showed epipapillary and subretinal fibrosis, respectively. Scleral buckle was performed for left non-rhegmatogenous retinal detachment which then improved and has been stable. Conclusions and Importance: We present a rare case of JS with some unique ophthalmic features which expand clinical knowledge on this complex systemic and ocular entity.